Otolaryngology needs among an adult homeless population: a prospective study - Vincent Wu; Christopher W. Noel; David Forner; Florence Mok; Molly Zirkle; Antoine Eskander; Vincent Lin; John M. Lee (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Homeless individuals frequently experience poor access to healthcare, delayed clinical presentation, and higher disease burden. Providing subspecialty otolaryngology care to this population can be challenging. We previously reported on the prevalence of hearing impairment in Toronto’s homeless community. As a secondary objective of this study, we sought to define otolaryngology specific need for this population. Methods One hundred adult homeless individuals were recruited across ten homeless shelters in Toronto, Canada using a stratified random sampling technique. An audiometric evaluation and head and neck physical examination were performed by an audiologist and otolaryngology resident, respectively. Basic demographic and clinical information was captured through verbal administration of a survey. Descriptive statistics were used to estimate frequency of otolaryngology specific diseases for this population. Results Of the 132 individuals who were initially approached to participant, 100 (76%) agreed. There were 64 males, with median age of 46 years (IQR 37–58 years). The median life duration of homelessness was 24 months (IQR 6–72 months). Participants had a wide range of medical comorbidities, with the most common being current tobacco smoking (67%), depression (36%), alcohol abuse (32%), and other substance abuse (32%). There were 22 patients with otolaryngology needs as demonstrated by one or more abnormal findings on head and neck examination. The most common finding was nasal fracture with significant nasal obstruction (6%). Eleven patients required referral to a staff otolaryngologist based on concerning or suspicious findings, including two head and neck masses, 6 were later seen in follow-up. Conclusion There were substantial otolaryngology needs amongst a homeless population within a universal healthcare system. Future research should focus on further elucidating head and neck related issues in this population and expanding the role of the otolaryngologist in providing care to homeless individuals.